Direct induction of neural progenitor cells transiently passes through a partially reprogrammed state. (March 2017) - Gao, Rui; Xiu, Wenchao; Zhang, Linfeng; Zang, Ruge; Yang, Lei; Wang, Chenfei; Wang, Min; Wang, Mingzhu; Yi, Li; Tang, Yuanyuan; Gao, Yawei; Wang, Hong; et al.
Abstract: The generation of functional neural progenitor cells (NPCs) holds great promise for both research and clinical applications in neurodegenerative diseases. Traditionally, NPCs are derived from embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs), or NPCs can be directly converted from somatic cells by sets of transcription factors or by a combination of chemical cocktails and/or hypoxia. However, the ethical issues of ESCs, the risk of tumorigenesis from iPSCs and transgenic integration from exogenous genes as well as complicated manipulation and time-consuming of chemical induced NPCs (ciNPCs) limit the applications of these strategies. Here, we describe a novel method for generating growth factor-induced neural progenitor cells (giNPCs) from mouse embryonic and adult fibroblasts by using inductive and/or permissive signaling culture conditions. These giNPCs closely resemble brain-derived NPCs in terms of transcription networks and neural lineage differentiation potentials. Moreover, this somatic cell to NPC induction is a gradual process that includes initiation, intermediate, maturation and stabilization stages. Importantly, gene expression and histone modification analyses further indicate a partially reprogrammed state during the generation process of induced NPCs, in which lineage specific genes and pluripotency associated genes are transiently activated. Our study therefore describes the potential safety problems that also exist in the transgene-free direct induction strategy and highlights the importance of excluding the possibility of residual partially reprogrammed and/or teratoma-like cells from the generated NPCs for future clinical trials.